THE MAKING OF ELECTRONIC ARCHIVES BASED ON MICROSOFT ACCESS AT DIII OFFICE ADMINISTRATION INSTITUT BISNIS DAN INFORMATIKA STIKOM SURABAYA - Marya Mujayana1, Marya Mujayana1; Ananda Cyndy Astanaria T., Ananda Cyndy Astanaria T. (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2019)
Archiving is very important in office activities because the archive is the memory center for every activity in the office. However, in the handling of archives, DIII Office Administration of Institut Bisnis dan Informatika Stikom Surabaya is still not efficient because it still implements a conventional filing system and is time consuming for rediscovery. This study aims to make electronic archiving using Microsoft Access that can facilitate the rediscovery of archives more effectively and efficiently. The use of Microsoft access is expected to help the office administration department to be able to manage records effectively and efficiently by using electronic media in the management of archives to obtain the benefits of speed, convenience and accuracy.